Residual sexuality and its seasonal variation in natural apomictic Paspalum notatum accessions - Rebozzio, Romina Natalia (2011)
Traditionally, tetraploid Paspalum notatum was considered an obligate or a facultative apomict according to cytoembryological analyses. The degree of facultativeness was usually determined by the relative amount of mature ovules bearing aposporous or meiotic (sexual) embryo sacs, or both together. We established, through progeny tests conducted with the aid of AFLP markers, the degree of residual sexuality expressed in four selected biotypes. The results showed it to be substantially and significantly lower than predicted by previous embryological analyses for the same biotypes. Moreover, the lowest expression of residual sexuality was coincident with maximum flowering period. Seed development in facultative apomictic P. notatum shows a definite bias against meiotic embryo sacs.